High Relative Frequency of Enteroaggregative Escherichia coli Among Patients With Reportable Enteric Pathogens, Minnesota, 2016–2017. (15th October 2018) - Beczkiewicz, Aaron; Cebelinski, Elizabeth; Decuir, Marijke; Lappi, Victoria; Wang, Xiong; Smith, Kirk; Boxrud, Dave; Medus, Carlota
Abstract: Background: Enteroaggregative Escherichia coli (EAEC) is increasingly recognized as an enteric pathogen as clinical laboratories transition to culture-independent diagnostic tests that detect EAEC. To date, epidemiological studies have focused on children aged <5 years, and information on EAEC incidence, illness outcomes, and transmission avenues is limited. Methods: Enteric disease surveillance data in Minnesota were used to describe EAEC illnesses reported to the Minnesota Department of Health from September 2016 through August 2017. We determined laboratory characteristics of EAEC using pulsed-field gel electrophoresis and next-generation sequencing. Frequency of EAEC illness, demographic profile of cases, clinical characteristics of illness, and plausible food or environmental exposures leading to EAEC transmission were assessed. Results: During the study period, 329 EAEC cases were reported. Among a subset of health systems able to detect EAEC over the entire study, EAEC was the second most common reportable enteric pathogen detected after Campylobacter and the most detected diarrheagenic E. coli pathotype. No other reportable enteric pathogens were detected among 75.3% of EAEC cases, and 68% of cases reported no international travel before onset. Several virulence genes were associated with clinical characteristics. Conclusions: We provide evidence that EAEC is a likely causative agent of diarrheal illness in the United States. Our study contributes to criteria development for identification of pathogenic EAEC and proposes potential exposure avenues. Abstract : We provide evidence that enteroaggregative Escherichia coli (EAEC) is an important cause of diarrheal illness in Minnesota. Sixty-eight percent of EAEC cases in our study were domestically acquired. Several virulence genes were associated with clinical characteristics.